COMPOUNDS AND XENOBIOTICS ALIEN TO ORGANISMS - Khitaev Boysin; Rozikova Mohira Odinaevna; Khitaeva Khafiza Boysinovna (Scholar Express Journals, 2021)
As a result of human economic activity, a large number of various xenobiotics, alien to humans and animals, circulate in the biosphere, many of which have extremely high toxicity. Entering the environment in significant quantities, they can affect the genetic apparatus of organisms, cause their death, and disrupt the balance of natural processes in the biosphere. At present, attempts are being made to reduce the level of the body's influence by xenobiotics by increasing the efficiency of the defense systems, this is especially important for children
Keywords: Xenobiotics; mutation; toxicoinfection; correction